DAMPAK KEBERADAAN WISATA RUMEDE TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA KUNYI KECAMATAN ANREAPI KABUPATEN POLEWALI MANDAR - Egi, Gifari Muhaimin; Falihin, Dalilul (xxxx-xxxx, 2025)
This study aims to determine: 1). How to describe the existence of rumede tourism in Kunyi Village, Anreapi District, Polewali Mandar Regency. 2). Knowing how the description of community welfare in Kunyi Village, Anreapi District, Polewali Mandar Regency. 3). Knowing the impact of developing rumede tourism in Kunyi Village, Anreapi District, Polewali Mandar Regency. The research is qualitatively descriptive. The data collection techniques used by researchers include: observation, in-depth interviews, and documentation. Researchers conducted the data collection process, encompassing collection, reduction, presentation, and drawing conclusions. The findings of this study indicate 1). The description of the existence of rumede tourism in Kunyi Village, Anreapi District, Polewali Mandar Regency has developed. This can be seen from the number of facilities that are increasing, such as prayer rooms, toilets, halls, gazebos, visitor parking areas, and places to rent camping equipment. The attractiveness of the Rumede tourist attraction is in terms of its unspoiled location and easily accessible by both local and foreign tourists. 2). Related to efforts to increase community welfare, it was concluded that the efforts made were developing the infrastructure of Kunyi Village, developing tourism in Kunyi Village, improving the quality of human and family resources and managing the life of the people of Kunyi Village so that they feel safe. In implementing these efforts, there are several aspects to be used for evaluation, namely aspects of education, health aspects and income aspects. 3). The results showed that there were positive and negative impacts from the development of the Rumede tourist attraction in Kunyi Village, Anreapi District, Polewali Mandar Regency. The positive impact is the impact on local people's income, the impact on employment and business opportunities and the impact on development in general. Apart from that, there are also negative impacts from the development of the Rumede tourist attraction, namely the impact on the environment around the Rumede tourist attraction. In the economic sector, there was an increase in the livelihoods of the surrounding community, as a result the income received by the community has increased compared to before.